Current summary of clinical studies on anti-TSLP antibody, Tezepelumab, in asthma - Momoko Kurihara; Hiroki Kabata; Misato Irie; Koichi Fukunaga (Allergology International, 2023)
Thymic stromal lymphopoietin (TSLP) is an epithelial cell-derived cytokine that plays a vital role in the induction of type 2 inflammation via both innate and acquired immune cascades. Tezepelumab, a human IgG2 monoclonal antibody that inhibits the binding of TSLP to the TSLP receptor, is the latest biologic for asthma. To evaluate the efficacy and mechanism of tezepelumab in asthma, the PATHWAY, NAVIGATOR, NOZOMI, UPSTREAM, CASCADE, SOURCE, and DESTINATION studies have been conducted. These results suggested that tezepelumab is a broad-target biologic, which is expected to be effective in patients with poorly controlled moderate to severe asthma regardless of the phenotype, although its efficacy in oral corticosteroids-dependent asthma, biological mechanism in non-type 2 phenotype, and long-term safety remain unknown. In this review, we summarize the results of clinical trials of tezepelumab in asthma and discuss the differences between tezepelumab and other biologics.